Changes in the regulation of public social-service institutions as a condition for private provision of social services - Kamnar, Helena (Družboslovne razprave, 1999)
The article deals with the view that public social-service institutions are a barrier to the major development of the provision of private social services in Slovenia. In addition to the public service for which they were intended and created by the state or municipality, they also carry out services in the private sector, in the same way as commercial companies and private non-profit organisations. The regulation of ownership, governance and financial structure of public social-service institutions do not sufficiently take this fact into account, which places these institutions in an unequal position when compared with other providers of social services. They are negatively discriminated with regard to their ownership and governance structures, while their financial structure remains, as a rule, in a privileged position. Such regulation of public institutions impedes the development of the private sector. Furthermore, the vague definition of public services and improper regulations place too heavy a burden on public finances. The author suggests a change in the regulation of public institutions and, consequently, also a change of the role of the state. There will be three models drawn up for providers of social services: state institutions exclusively bound to public services, public and private providers having a concession, and public institutions providing public services, as well as services on the market.
Keywords: družbene dejavnosti; neprofitne organizacije; public sector; javni sektor; zasebni sektor